2021
DOI: 10.1016/j.pmedr.2021.101532
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma detection by skin self-examination targeting at-risk women: A randomized controlled trial with telemedicine support for concerning moles

Abstract: Highlights At-risk women receiving online skin self-examination education initiated mole checks. Women receiving skin self-examination education sought health care when necessary. Provided education increased confidence in mole checking and did not affect anxiety. Women trained to do skin checks had fewer appointments for benign mole than controls. Detection of early melanomas was facilitated by skin self-examination e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A total of 1566 studies were identified in the database search. After removing duplicates, the screening process, and complete reading of the records that met the eligibility criteria, 17 RCTs were finally included in the review [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The complete process is shown in Figure 1.…”
Section: Study Selection and Methodological Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 1566 studies were identified in the database search. After removing duplicates, the screening process, and complete reading of the records that met the eligibility criteria, 17 RCTs were finally included in the review [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The complete process is shown in Figure 1.…”
Section: Study Selection and Methodological Quality Assessmentmentioning
confidence: 99%
“…The age of the participants ranged from 12.6 to 54.3 years. The digital strategies used in the included RCTs were web-based interventions in 8 studies [35,40,42,43,46,[48][49][50], 6 involved apps [36][37][38]44,45,47], 3 involved SMS [35,36,39], 2 involved video [34,41], and 1 involved a wearable device [47]. Conversely, the comparator groups involved no intervention in 11 studies [35,37,[43][44][45][46][47][48]50] and active controls in 6 studies [34,36,38,39,41,49].…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations